2021
DOI: 10.2991/ahe.k.210205.093
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Digital Marketing for UKM in Facing the Covid-19 Pandemic

Abstract: The Covid-19 pandemic has changed many things, in one country and in an economic area that has declined or even collapsed. Social restrictions imposed in an area have decreased the level of sales for UKM. Work From Home (WFH) is one of the factors that cause consumers not to want to make purchases offline. Large-scale Social Restrictions (PSBB) caused almost all shops to close, this greatly affected product sales for UKM players. Responding to this, UKM is trying hard to find ways to increase sales, one soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The use of advertising (ads) on social media requires initial capital, but the benefits obtained are comparable and can even significantly exceed the capital used is problematic. This is because using advertising can reach consumers better based on the criteria we have previously set, based on age, place of origin, profession, gender, and even which accounts are usually seen by the target customer (Meileni,et al, 2021). c. Create and publish marketing product videos, then stream them from social media accounts or run direct promotions of the products sold so that consumers can see them following the social media of MSME actors.…”
Section: Resultsmentioning
confidence: 99%
“…The use of advertising (ads) on social media requires initial capital, but the benefits obtained are comparable and can even significantly exceed the capital used is problematic. This is because using advertising can reach consumers better based on the criteria we have previously set, based on age, place of origin, profession, gender, and even which accounts are usually seen by the target customer (Meileni,et al, 2021). c. Create and publish marketing product videos, then stream them from social media accounts or run direct promotions of the products sold so that consumers can see them following the social media of MSME actors.…”
Section: Resultsmentioning
confidence: 99%
“…The potential in the Tempe Sanan Malang SMEs group is that their products are in great demand by tourists, both local and international. Digitalization efforts will increase income while increasing popularity (Meileni et al, 2021). Through creative digitalization packaging for SMEs, this correlates with increasing opportunities to win competition in the creative economy sector (Chollisni et al, 2022;Sopanah et al, 2018), especially in culinary terms.…”
Section: Identification and Mapping Of Smes Digitalization Potentialmentioning
confidence: 99%
“…The village chief suggested that products initially directed to the tourism market continue to be produced due to market online demand [74]. To this point, the online marketing model has become an essential key to recognizing the products of the PwSAs locally, regionally, nationally, and internationally [75].…”
Section: Economic Conditions Before and During Covid-19 Pandemicmentioning
confidence: 99%